2017
DOI: 10.3390/biom7030061
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Cancer: Mechanisms and Therapies

Abstract: Several scientific and clinical studies have shown an association between chronic alcohol consumption and the occurrence of cancer in humans. The mechanism for alcohol-induced carcinogenesis has not been fully understood, although plausible events include genotoxic effects of acetaldehyde, cytochrome P450 2E1 (CYP2E1)-mediated generation of reactive oxygen species, aberrant metabolism of folate and retinoids, increased estrogen, and genetic polymorphisms. Here, we summarize the impact of alcohol drinking on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 156 publications
1
93
0
2
Order By: Relevance
“…A loss of retinoic acid has a negative effect on cell differentiation and thus enhances carcinogenesis [30]. Moreover, ethanol increases cellular membrane permeability and acts as a solvent to facilitate penetration of (pro-)carcinogens into the intracellular domain of mucosal epithelial cells [5,14,15]. High-risk alcohol drinkers who smoke should be advised to quit alcohol and tobacco and should consider going for a screening oesophagogastroduodenoscopy.…”
Section: Oesophageal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…A loss of retinoic acid has a negative effect on cell differentiation and thus enhances carcinogenesis [30]. Moreover, ethanol increases cellular membrane permeability and acts as a solvent to facilitate penetration of (pro-)carcinogens into the intracellular domain of mucosal epithelial cells [5,14,15]. High-risk alcohol drinkers who smoke should be advised to quit alcohol and tobacco and should consider going for a screening oesophagogastroduodenoscopy.…”
Section: Oesophageal Cancermentioning
confidence: 99%
“…The main component of alcoholic drinks is ethanol. Once ingested, alcohol (ethanol) is metabolized by alcohol dehydrogenase (ADH) into acetaldehyde, which by aldehyde dehydrogenase (ALDH) is then oxidized to acetate [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is the most affected organ, since ethanol is mostly metabolized there [11,13], but gastrointestinal, central, and peripheral nervous systems; the heart and vascular system; endocrinological systems; nutrition; and musculo-skeletal systems are clearly affected [10]. In addition, ethanol is an immunosuppressive drug that is pro-inflammatory and pro-oncogenic [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Surely, even though mechanisms underlying alcohol-related carcinogenesis are not completely elucidated, different studies showed that chronic alcohol consumption, especially for high doses, could cause the onset of cancers(45)(46)(47).The mechanisms of alcohol on tumorigenesis include the production of acetaldehyde (derived from ethanol metabolism), oxidative stress, effects on metabolism, endocrine and immunity system, together with the influence of genetic polymorphisms regulating the absorption and the metabolic pathway of this substance (45-47). A multitude of genes contribute to the correct metabolism of alcohol, like those for ADH, ADLH, CYP2E1, and methylene-tetrahydrofolate reductase (MTHFR).…”
mentioning
confidence: 99%